Delayed Diagnosis of Blunt Ureteral Injury following Motor Vehicle Collision - Alexander Canales; Harsh Desai (Case Reports in Surgery)
Background. A 19-year-old male requiring emergency surgery after presenting to the emergency department (ED) as a trauma activation status post-motor vehicle collision. Summary. The patient presented to the ED after a motor vehicle collision. He was taken emergently to the operating room after finding hemoperitoneum on computerized tomography scan without evidence of solid organ injury. Significant small and large bowel injuries were discovered requiring resection and anastomosis. The patient had an uneventful post-operative recovery and was discharged home. He was later re-admitted to the hospital with a large pelvic abscess and a left mid-ureteral stricture causing hydronephrosis. The abscess was treated with antibiotics, and the left ureteral injury was treated with a nephrostomy tube and stent placement. He made a full recovery after hospital re-admission and a delay in diagnosis of blunt ureteral injury. Conclusion. Patients involved in motor vehicle collisions are at risk of multi-system trauma including genito-urinary injuries. A small percentage of these patients may present with blunt ureteral injuries. A high index of suspicion is required to make an early diagnosis. Earlier diagnosis may help to prevent morbidity.